Risk Factors of Postpartum Depression - Nana Usnawati; Nuryani Nuryani (Alliance oh Health Activists (AloHA), 2019)
Postpartum depression is a relatively severe depression that occurs after delivery. The purpose of this study is to analyze the influence of maternal factors and social support on postpartum depression. This study used a cross-sectional design. The population was postpartum mothers in Ngariboyo, Magetan Regency with a sample size of 100 respondents. Samples were taken by consecutive sampling. Data were collected with the Indonesian version of the EPDS questionnaire and husbands' social support. Data were analyzed using logistic regression test. The prevalence of postpartum depression in Ngariboyo Community Health Center, Magetan used the EPDS were 49 mothers (49%). The result of this research showed that there risk factors for depression in the postpartum mother were parity, work, and support of the husband. The most influential factor was parity (p = 0.004; OR 3.709). The conclusion of this research was the smaller of parity, the higher the risk of postpartum depression. Working mothers were the higher of the risk of postpartum depression. The lower the husband support, the higher the risk of postpartum depression. Counseling during pregnancy with the involvement of husbands needs to be improved as an effort to prevented postpartum depression. Keywords: age; parity; work; husband support; postpartum depression